2021
DOI: 10.1029/2021gl095247
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Ambient Organic Gases to Inorganic Salt Solutions: Influence of Salt Identity, Ionic Strength, and pH

Abstract: It is well established that the identity and concentration of inorganic salts play a determining role in organic solubility. For example, in the 19th century, Hofmeister observed a repeatable salt pattern that describes the ability of ions to cause proteins (organic molecules) to "salt in" or "salt out," (Gurau et al., 2004;Kunz et al., 2004) though controlling mechanisms are still debated (Y. Zhang & Cremer, 2006).Despite the ubiquity and importance, accurate quantitative description of the partitioning of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Ionic strength and inorganic salts in aerosol deliquescent particles can strengthen or weaken the solubility of organic gases, referred to as “salting in” and “salting out” effects, respectively. However, in this study, we could not identify the effect of inorganic ions on the uptake of PAN, as no significant correlations were found between the liquid concentrations of inorganic ions (SO 4 2– , NO 3 – , Cl – , and NH 4 + ) and PAN uptake coefficient ( p > 0.05).…”
Section: Resultsmentioning
confidence: 72%
“…Ionic strength and inorganic salts in aerosol deliquescent particles can strengthen or weaken the solubility of organic gases, referred to as “salting in” and “salting out” effects, respectively. However, in this study, we could not identify the effect of inorganic ions on the uptake of PAN, as no significant correlations were found between the liquid concentrations of inorganic ions (SO 4 2– , NO 3 – , Cl – , and NH 4 + ) and PAN uptake coefficient ( p > 0.05).…”
Section: Resultsmentioning
confidence: 72%
“…Several studies examining gas-particle partitioning of atmospheric organic acids have also reported similar modelmeasurement discrepancies. 32,[89][90][91][92][93][94] Proposed explanations include the strong effect of activity coefficients and the formation of complexes or organic salts. Both could contribute to the discrepancies observed here for PFCAs.…”
Section: Implications For Understanding Pfca Gas-particle Partitioningmentioning
confidence: 99%
“…Oxalic acid also exhibited similar results for the relationships between ε­(C 2 O 4 2– ) and the key driving factors, whereas its relationships with SO 4 2– and T differed from those of Fp with SO 4 2– and T (Figures S10 and S11). Sulfate plays an important role in oxalic acid uptake through its influence on pH and ALWC as well as through its “salting in” effect on the precursors of oxalic acid (e.g., glyoxal), particularly in high ALWC conditions. , In both PEs, T negatively correlated with ε­(C 2 O 4 2– ), indicating that low T results in condensation of oxalic acid molecules to their aerosol phase.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfate plays an important role in oxalic acid uptake through its influence on pH and ALWC as well as through its "salting in" effect on the precursors of oxalic acid (e.g., glyoxal), particularly in high ALWC conditions. 37,38 In both PEs, T negatively correlated with ε(C 2 O 4 2− ), indicating that low T results in condensation of oxalic acid molecules to their aerosol phase.…”
Section: Oxalic Acid Partitioning Behavior During Pesmentioning
confidence: 99%